Analisis Komitmen Organisasi, Disiplin Kerja & Lingkungan Kerja Terhadap Kinerja Pegawai di Masa Pandemi Covid-19 - Ahmadi Ahmadi; Toto Hardiyanto (The Graduate School of Sahid University, 2021)
The cutting and postponement of Regional Performance Allowances during the Covid-19 pandemic had an impact on the performance of Civil Servants. This study aims to analyze the effect of organizational commitment, work discipline and work environment on performance and formulate strategies to improve performance during the Covid-19 pandemic by taking a case study at the Central Jakarta City Fire and Rescue Agency. This study uses a quantitative approach with data collection techniques through surveys, by distributing questionnaires to 56 respondents with sample criteria through non-probability sampling techniques. The results showed that the three independent variables had a significant influence on the dependent variable and the preferred strategy was the